2013
DOI: 10.1111/aas.12118
|View full text |Cite
|
Sign up to set email alerts
|

Epidural vs. intravenous fentanyl during colorectal surgery using a double‐blind, double‐dummy design

Abstract: During major abdominal surgery, epidural administration requires lower doses of intraoperative fentanyl when compared with the intravenous route. Epidural fentanyl also facilitates early awakening and residual analgesia without increasing adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It was well-known that both PCEA and PCIA are applicable to the analgesia of spinal fusion, while there remains a controversy for the optimal method for the postoperative pain relief [12,27]. Recently, several previous studies have indicated that PCEA is more effective than PCIA for the analgesia of spinal fusion [28][29][30][31]. Nevertheless, there are also some studies that showed discordant results [14,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…It was well-known that both PCEA and PCIA are applicable to the analgesia of spinal fusion, while there remains a controversy for the optimal method for the postoperative pain relief [12,27]. Recently, several previous studies have indicated that PCEA is more effective than PCIA for the analgesia of spinal fusion [28][29][30][31]. Nevertheless, there are also some studies that showed discordant results [14,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In a human study with fentanyl administered by intravenous route or epidural route, similar sedation results were achieved with both treatments, suggesting that fentanyl might also undergo a rapid systemic uptake (Sadurní and others 2013). Comparably, the rapid systemic effect of epidural methadone may be due to the rapid absorption by blood vessels of the epidural space and rapid distribution into the systemic circulation (Haroutiunian and others 2014).…”
Section: Discussionmentioning
confidence: 90%
“…This shorter duration probably occurred because the authors used half the dose of local anaesthetic bupivacaine in the BupFent treatment than in the Bup treatment. Fentanyl epidural alone (0.002 mg/kg) in human beings had an average analgesic duration of five hours (Sadurní and others 2013), which is more than twice as long as that experienced when the same dose was administered intravenously (two hours). In the present study, the analgesic duration of epidural fentanyl was much shorter.…”
Section: Discussionmentioning
confidence: 99%
“…There are also contradictory results regarding the effectiveness of epidural vs. intravenous fentanyl [28,29]. Epidural fentanyl has been suggested to have both systemic and spinal actions.…”
Section: Discussionmentioning
confidence: 99%